Somatostatin does not reduce oesophageal variceal pressure in liver cirrhotics. Issue 2 (February 1988) - Kleber, G; Sauerbruch, T; Fischer, G; Paumgartner, G
Abstract : Transmural oesophageal variceal pressure was determined by direct puncture of the varices in 27 patients with liver cirrhosis and oesophageal varices. Variceal pressure was not influenced three to six minutes after somatostatin bolus administration and slightly increased during somatostatin infusion. Thus, potential haemostatic benefits of somatostatin cannot be explained by pressure reductions in the varices.